2022
DOI: 10.3390/cells11040691
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of L-Dopa-Induced Dyskinesias by MPEP Blockade of Metabotropic Glutamate Receptor 5 Is Associated with Reduced Inflammation in the Brain of Parkinsonian Monkeys

Abstract: Proinflammatory markers were found in brains of Parkinson’s disease (PD) patients. After years of L-Dopa symptomatic treatment, most PD patients develop dyskinesias. The relationship between inflammation and L-Dopa-induced dyskinesias (LID) is still unclear. We previously reported that MPEP (a metabotropic glutamate receptor 5 antagonist) reduced the development of LID in de novo MPTP-lesioned monkeys. We thus investigated if MPEP reduced the brain inflammatory response in these MPTP-lesioned monkeys and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 122 publications
2
9
0
Order By: Relevance
“… Ohlin et al (2011) using post-mortem basal ganglia tissue from PD patients and a brain tissue from a rat model of LID revealed increased angiogenesis, up-regulation of vascular endothelial growth factor, and altered brain-blood barrier properties. Other pre-clinical studies have shown an inflammatory environment in the dopamine-depleted striatum, with sustained activation of astrocytes, microglia, cicloxigenase-2 (COX-2), and recruitment of immune elements contributing to the pathophysiology of LID ( Bortolanza et al, 2015a , 2021 ; Del-Bel et al, 2016 ; Morissette et al, 2022 ; Mulas et al, 2016 ; Zhang et al, 2021 ). Supporting this hypothesis, long after the neurotoxin 6-hydroxydopamine (6OHDA) has been cleared from the brain, the striatum of lesioned rats receiving L-DOPA treatment displayed sustained neuroinflammation signals ( Bortolanza et al, 2015a , 2015b , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… Ohlin et al (2011) using post-mortem basal ganglia tissue from PD patients and a brain tissue from a rat model of LID revealed increased angiogenesis, up-regulation of vascular endothelial growth factor, and altered brain-blood barrier properties. Other pre-clinical studies have shown an inflammatory environment in the dopamine-depleted striatum, with sustained activation of astrocytes, microglia, cicloxigenase-2 (COX-2), and recruitment of immune elements contributing to the pathophysiology of LID ( Bortolanza et al, 2015a , 2021 ; Del-Bel et al, 2016 ; Morissette et al, 2022 ; Mulas et al, 2016 ; Zhang et al, 2021 ). Supporting this hypothesis, long after the neurotoxin 6-hydroxydopamine (6OHDA) has been cleared from the brain, the striatum of lesioned rats receiving L-DOPA treatment displayed sustained neuroinflammation signals ( Bortolanza et al, 2015a , 2015b , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The onset and progression of LID are also thought to depend on other pro-inflammatory factors, such as cytokines released by activated glial cells. This is the case in both rodents ( Del-Bel et al, 2016 ; Carta et al, 2017 ; Pisanu et al, 2018 ; Junior et al, 2020 ) and non-human primates ( Morissette et al, 2022 ). In the present study, we show that the 20-mg.kg −1 dose of Doxy totally prevented the rise in striatal TNF-α observed in dyskinetic mice and only partially that of IL-1β.…”
Section: Discussionmentioning
confidence: 96%
“…The neurotransmitter imbalance in the basal ganglia of dyskinetic animals also leads to neuroinflammation, another critical hallmark of LID ( Del-Bel et al, 2016 ; Carta et al, 2017 ; Pisanu et al, 2018 ; Morissette et al, 2022 ). Experimental data collected over recent years revealed, for instance, that pro-inflammatory enzymes, such as cyclooxygenase-2 (COX-2) and the inducible nitric oxide synthase (iNOS), are activated in the basal ganglia structures of rodents with l -DOPA-induced AIMs ( Bortolanza et al, 2015a ; Bortolanza et al, 2015b ).…”
Section: Introductionmentioning
confidence: 99%
“…It is now well‐acknowledged that chronic neuroinflammation occurs concurrently with PD pathology and may contribute to DA neuron degeneration (Gelders et al., 2018; McGeer et al., 1988; Qian et al., 2010). Conceivably, as recently suggested, neuroinflammation may also be mechanistically linked to the development of LIDs (Morissette et al., 2022; Mulas et al., 2016; Rentsch et al., 2020). In particular, Morissette et al.…”
Section: Introductionmentioning
confidence: 90%
“…It is now well-acknowledged that chronic neuroinflammation occurs concurrently with PD pathology and may contribute to DA neuron degeneration (Gelders et al, 2018;McGeer et al, 1988;Qian et al, 2010). Conceivably, as recently suggested, neuroinflammation may also be mechanistically linked to the development of LIDs (Morissette et al, 2022;Mulas et al, 2016;Rentsch et al, 2020). In particular, Morissette et al found a positive correlation between dyskinesia scores and all (IBA1+) and activated (CD68+) microglia in the putamen of MPTP lesioned monkeys and Mulas et al demonstrated an increase in activated microglia only in rats that received a L-Dopa regime leading to LID (Morissette et al, 2022;Mulas et al, 2016).…”
Section: Introductionmentioning
confidence: 92%